ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI PIJAT TUI NA UNTUK MENINGKATKAN PEMENUHAN KEBUTUHAN NUTRISI PADA BALITA YANG MENGALAMI KESULITAN MAKAN - Sintya Marliani Putri (2022)
Feeding difficulties is a general term that covers a variety of feeding problems, including the feeding process in children. One of the non-pharmacological therapies that is starting to be widely used to overcome eating difficulties in children is massage therapy using the Tui Na massage technique. The purpose of writing this scientific paper is to analyze nursing care with Tui Na massage therapy to increase the fulfillment of nutritional needs for toddlers at Bhayangkara TK. I R. Said Sukanto Hospital who has difficulty eating. This study compared managed patients who were given basic nursing care and additional Tui Na massage therapy interventions with resume patients who were only given basic nursing care. The instruments used in this study were a questionnaire on eating difficulties and a CEBQ (Children Eating Behavior Questionnaire) questionnaire to assess the presence of eating difficulties in toddlers and an observation sheet on food intake to observe changes in the fulfillment of nutritional needs in patients. Tui Na massage therapy intervention was carried out for 10-30 minutes in one session according to Standard Operating Procedures. The results obtained showed an increase in the fulfillment of nutritional needs, a decrease in difficulty eating scores and an increase in body weight in patients who were given the Tui Na massage intervention, so it can be concluded that the Tui Na massage therapy given can help increase the fulfillment of nutritional needs in toddlers as well as help overcome difficulties. eat. However, the implementation of the intervention which should be carried out in 1 set, i.e. once a day for 6 days, was only carried out for 3 days, and the intervention carried out on children in treatment who also received pharmacological interventions created a bias in the results of the intervention and became a drawback in this study.